2009
DOI: 10.1371/journal.pone.0005661
|View full text |Cite
|
Sign up to set email alerts
|

Shellfish Face Uncertain Future in High CO2 World: Influence of Acidification on Oyster Larvae Calcification and Growth in Estuaries

Abstract: BackgroundHuman activities have increased atmospheric concentrations of carbon dioxide by 36% during the past 200 years. One third of all anthropogenic CO2 has been absorbed by the oceans, reducing pH by about 0.1 of a unit and significantly altering their carbonate chemistry. There is widespread concern that these changes are altering marine habitats severely, but little or no attention has been given to the biota of estuarine and coastal settings, ecosystems that are less pH buffered because of naturally red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
266
2
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(292 citation statements)
references
References 33 publications
15
266
2
4
Order By: Relevance
“…arag of 3.44. Recognizing that carbonate chemistry can be variable over diel and seasonal timescales Feely et al, 2008;Miller et al, 2009), we suggest that the typical diel and seasonal range of values of aragonite saturation state be incorporated into this boundary (i.e., > 80% of the average surface ocean, preindustrial aragonite saturation state +/-diel and seasonal variability). The major rationale behind this subjective value is twofold: to keep high-latitude surface waters above aragonite under-saturation and to ensure adequate conditions for most coral systems.…”
Section: Ocean Acidificationmentioning
confidence: 94%
See 1 more Smart Citation
“…arag of 3.44. Recognizing that carbonate chemistry can be variable over diel and seasonal timescales Feely et al, 2008;Miller et al, 2009), we suggest that the typical diel and seasonal range of values of aragonite saturation state be incorporated into this boundary (i.e., > 80% of the average surface ocean, preindustrial aragonite saturation state +/-diel and seasonal variability). The major rationale behind this subjective value is twofold: to keep high-latitude surface waters above aragonite under-saturation and to ensure adequate conditions for most coral systems.…”
Section: Ocean Acidificationmentioning
confidence: 94%
“…The projected rate of change in ocean CO 2 chemistry leaves little time for organisms to evolve adaptations. While some species may be CO 2 -insensitive or able to adapt (e.g., Miller et al, 2009), the energetic costs of achieving net shell growth and preventing dissolution in conditions of aragonite under-saturation will likely have other impacts on overall growth rates, predation, metabolism or reproduction, as observed in organisms from other regions (e.g., Iglesias-Rodriguez et al, 2008;Fabry et al, 2008;Wood et al, 2008;Tunnicliffe et al, 2009).…”
Section: Ocean Acidificationmentioning
confidence: 99%
“…Numerous studies on bivalve molluscs showed reduced rates of calcification in response to ocean acidification (e.g. Miller et al 2009;. Marine organisms display a species-specific ability to calcify (Ries et al 2009, Findlay et al 2011, probably linked to their ability to maintain favorable chemical condition for CaCO 3 precipitation at the calcification site when exposed to high pCO 2 (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that OA stress impaired the energy metabolic pathways in oysters, and also retarded the normal growth and development [23,24]. However, the impact of OA on the immune responses of oysters has received little attention so far.…”
Section: Introductionmentioning
confidence: 99%